Education on the Importance of Waste Sorting at SDN 009 Simpang Kubu as an Effort to Control Waste - Nur Asiah; Rani Rahmadini; Ahmad Fauzan; Fani Mustiana; Ganis N M Habeahan; Ilham Imanda; Lestari Handayani; Lestari Lature; Nur Atika Dewi; Yossy Juliana Gultom; Yanda Wilfidandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Simpang Kubu Village is one of the villages in Kampar District, Kampar Regency, Riau Province. In one of the elementary schools in Simpang Kubu Village, we Real Work Study Students conduct education at elementary schools in the village, namely at SDN 009 Simpang Kubu. The education delivered is related to waste sorting. Waste is a material that is wasted or disposed of from sources of human and natural activities that do not yet have economic value. The lack of concern of the Indonesian people regarding good waste sorting encourages us to conduct this education. This study aims to increase students' knowledge and awareness regarding how to sort waste properly and correctly according to existing waste categories.